The Influence of Management Information System Transition on Individual Impact Mediated by Perceived Ease of Use and Usefulness - Made Hizkia; Gede Ariadi (MIX: JURNAL ILMIAH MANAJEMEN, 2023)
Objectives: The aim of the research is to reveal how perceived usefulness and ease of use can bridge the gap among the impacts on individuals of information quality, system quality, and service quality.Methodology: This study uses a quantitative method to assess the theoretical model by asking several questions linked to Google Forms. This study utilized a quantitative analysis instrument by SmartPLS software. Partial Least Square-Structural Equation Modelling utilizes data analysis. The population of this study were employees at PT KIMI which moved to manufacture tire products in West Java with a total sample of 75 respondents. The data analysis used is the Partial Least Square-Structural Equation Model (PLS-SEM) by SmartPLS 3.0 software. The initial phase in data analysis is to summarize figures on the respondents' descriptions. The subsequent phase is to gauge the validity and reliability through discriminant validity and reliability tests.Finding: The study results showed that employees' perceived usefulness and ease of use mediate the relationship between information quality, system quality, and individual impact. Conversely, the service quality could not directly influence individual impact through perceived usefulness. Perceived ease of use and usefulness serially mediate the relationship between system quality, service quality, and individual impact. Conclusion: The perceived ease of use and usefulness variables can serially mediate the relationship between system quality and service quality on individual impact. Users of information systems will feel a more significant personal impact if perceived usefulness and ease of use are implemented to achieve comfortable working.